A comparative study of neuroprotective strategies and outcomes in neonatal hypoxic ischaemic encephalopathy - Kali, Gugulabatembunamahlubi Tenjiwe Jabulile (Stellenbosch : Stellenbosch University, 2021)
Thesis (PhD)--Stellenbosch University, 2021.